2009
DOI: 10.1007/s11250-009-9496-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of Simada sheep with graded levels of concentrate meal on feed intake, digestibility and body-weight parameters

Abstract: The experiment consisting of 7 days of digestibility and 90 days of feeding trial was conducted at Wogda (Ethiopia) to determine the effect of supplementation of graded levels of concentrate mix (CM) on feed intake, digestibility, and body weight (BW) change in hay-based feeding of Simada sheep. Twenty-yearling Simada sheep with a mean initial BW of 17.9 +/- 0.81 kg (mean +/- SD) were used in randomized complete block design arranged into five blocks of four animals. The four dietary treatments that consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
8
4
3
Order By: Relevance
“…The diff erence in the ADL content might be due to the diff erence in the proportion of grass species and stage of maturity at the harvest. The OM of grass hay in the current study was comparable with the result (107 g/kg) reported by Dessie et al (2010).…”
Section: As Illustrated Insupporting
confidence: 91%
See 3 more Smart Citations
“…The diff erence in the ADL content might be due to the diff erence in the proportion of grass species and stage of maturity at the harvest. The OM of grass hay in the current study was comparable with the result (107 g/kg) reported by Dessie et al (2010).…”
Section: As Illustrated Insupporting
confidence: 91%
“…The ADF content of hay obtained in this study was in an agreement with 468 g/kg DM reported by Abebaw and Solomon (2008), but higher than the value (445 g/kg DM) reported by Tafa et al (2010) and lower than the value (510 g/kg DM) reported by Dessie et al (2010). The ADL content of grass hay used in the current study was comparable to the result obtained by Dessie et al (2010), but higher than 43.6 and 56 g/kg DM reported by Tafa et al (2010) and Bishaw and Melaku (2008), respectively. The diff erence in the ADL content might be due to the diff erence in the proportion of grass species and stage of maturity at the harvest.…”
Section: As Illustrated Insupporting
confidence: 87%
See 2 more Smart Citations
“…Safflower meal is mainly used as an ingredient for animal feed due to its high protein content. In fact, several studies have shown that the incorporation of safflower meal into the feed of ruminants, such as sheep and cattle, improves their performances (Dixon et al, 2003a, b;Dessie et al, 2010). Barbour et al (2016) showed that the meal of dehulled safflower seeds could replace lysine supplementation in a soybean meal-based feed.…”
Section: Introductionmentioning
confidence: 99%